Local wisdom-based tourism development and communication strategy in Sayang Heulang beach - Nuryah Asri Sjafirah; Achmad Abdul Basith; Efi Fadilah; Dian Wardiana Sjuchro; Isni Nurfauzia; Nadhifa Viannisa (Faculty of Communications Science, Dr. Soetomo University, 2024)
Sayang Heulang Beach, a tourism destination on the southern coast of Garut Regency, holds a significant intangible cultural heritage encompassing the local wisdom of Mancagahar Village, Pameungpeuk Sub-District, and Garut in general. This research explored communication and promotional strategies for the development of Sayang Heulang Beach, using a qualitative approach based on its local wisdom. By conducting interviews with seven informants and validity data using the triangulation technique with Focus Group Discussion (FGD), the study revealed that the destination fulfilled the requirements of nature-based tourism, offering authenticity, uniqueness, locality, and an immersive cultural experience among the community. However, there were areas for improvement. The local wisdom from cultural, historical, and mythical perspectives was still in the exploration process, and budget limitations resulted in the absence of thorough target market identification. Moreover, communication messages and promotions did not address tourists' fundamental needs regarding functionality, symbolism, and memorable experiences.